DINÂMICA DO NITROGÊNIO INFLUENCIADA PELA ADUBAÇÃO NITROGENADA E ADIÇÃO DE GESSO EM SISTEMA PLANTIO DIRETO DE LONGA DURAÇÃO - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
Nitrogen is a nutrient with such a high contribution for agriculture, that various strategies are studied every year looking for enhancements of its use efficiency and reduction of its environmental impacts. This study hypothesis is that, the use of gypsum can change the soil’s nitrogen dynamic in the no-tillage system. So, the main objective of this study was to relate the dynamic of the labile compartments of C and N as indicators of fewer losses or lower efficiency of Nitrogen by the use of gypsum under a well-established no-till system. The objective was to relate the dynamics of labile compartments C and N as loss of reduction or efficiency indicators of N due to the use of gypsum in no-tillage system. The experiment was established in September 2012 on clay Oxisol in Ponta Grossa – PR, in a split-split plot completely randomized block design, with three replications. The sources of variation were used gypsum (plots), nitrogen (split-plots) and time (split-split plots). The corn sowing was done in September 2014. The treatments used in the plots were gypsum rates: a) absence of gypsum and b) 2.7 Mg ha-1 of gypsum applied surface. Treatments of subplots were: a) 0 kg ha-1 N; b) 80 kg ha-1 N; c) 160 kg ha-1 N and d) 240 kg ha-1 applied on corn at the V4 stage phenological (four leaves expanded). The time factor was inserted as split-split plots: a) 0 days after sowing (DAS); b) 34 DAS; c) 52 DAS; d) 87 DAS and e) 117 DAS. Within the first and the fifth time layers were sampled 0-5 cm, 5-10 cm, 10-20 cm, 20-40 cm and 40-60 cm. For intermediate times were sampled layers up to 20 cm. The variables analyzed were: a) Nitrate; b) hot water extractable organic carbon (HWEOC); c) permanganate oxidizable organic carbon (POXC); d) Total Organic Carbon (TOC) and e) Total Nitrogen (TN). It was also held for sampling density in the layers referred to only in the first season. Straw samples were collected for reading C and Total N was also evaluated the decomposition of crop residues. The corn production was studied in function of the treatments employed. The use of gypsum become an important tool to minimize the environmental impact nitrate leaching. In high fertility areas and therefore no chemical deterrents in depth to achieve high production ceilings, low doses of plaster do not provide increases in corn yields, but changes in labile compartments C are observed. In long term experiments changes should be seen in TOC and NT and consequently grain production in responses can be observed.
Nitrogen dynamics influenced by nitrogen fertilization and gypsum application under no-tillage
Keywords: lixiviação; nitrato; C-lábil; gesso; leaching; nitrate; labile carbon; gypsum; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA